Overtraining syndrome - what we already know - Brylinski, L.; Wolinski, F.; Duda, P.; Drozak, P.; Kostelecka, K.; Baj, J. (Journal of Education, Health and Sport, 2022)
Introduction: Overtraining syndrome (OTS) is a state of excess sportsmen's overload caused by too high an intensity of training. The main cause of OTS is too big a training load. Also, they are other risk factors like restrictive diets, inordinate stress, and inflated expectations of a family and a coach.